1999
DOI: 10.1016/s0014-5793(99)00196-9
|View full text |Cite
|
Sign up to set email alerts
|

Murine 12(R)‐lipoxygenase: functional expression, genomic structure and chromosomal localization1

Abstract: A cDNA, recently cloned (by Krieg et al. (1998)) from mouse skin, was shown to encode a 12(R)-lipoxygenase. When expressed in HEK cells, the recombinant protein converted methyl arachidonate into the corresponding 12-HETE ester which was shown to be the R-enantiomer by chiral phase chromatography. Neither arachidonic acid nor linoleic acid were substrates for the recombinant protein. The structure of the 12(R)-lipoxygenase gene is unique among all animal lipoxygenases in that it is divided into 15 exons and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 34 publications
(53 reference statements)
3
38
0
Order By: Relevance
“…Murine (12R)-LOX strongly prefers methylated polyenoic fatty acids (22,27). Here, we confirmed these data with three different substrates: arachidonic acid, linoleic acid, and 20-HETE.…”
Section: Enzymesupporting
confidence: 83%
See 2 more Smart Citations
“…Murine (12R)-LOX strongly prefers methylated polyenoic fatty acids (22,27). Here, we confirmed these data with three different substrates: arachidonic acid, linoleic acid, and 20-HETE.…”
Section: Enzymesupporting
confidence: 83%
“…12 for review), but little is known about the corresponding mechanisms of the more recently discovered R-lipoxygenating enzyme species (21)(22)(23). However, during the preparation of this manuscript, a study that also included two R-LOXs was published (24).…”
Section: Lipoxygenases (Loxs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some evidence suggests functions of LOX outside of the AA cascade, in that not only free PUFAs are a substrate for lipoxygenation reactions (6,(28)(29)(30). In addition, there are recent indications for functions of LOX that are independent of the enzymatic activity of individual LOXs (24,31).…”
Section: Discussionmentioning
confidence: 99%
“…ALOX12B was fi rst discovered in human ( 54 ) and mouse skin ( 55 ). Amino acid alignment of hALOX12B and nALOX12B indicated that from the 701 amino acids of hALOX12B, 524 (75%) were identifi ed in the Neandertal genome.…”
Section: Alox12b (12r-lox)mentioning
confidence: 99%